WEB BASED GEOGRAPHIC INFORMATION SYSTEMS PRODUCTIVE AND NON PRODUCTIVE LAND IN BALI - Made Tina Mulya Dewi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aimed to: (1) design a prototype geographic information system productive and non-productive land, (2) implement a geographical information system prototype productive and non-productive land. In the design and implementation, the researcher used AHP (Analysis Hierarchy Process) which has 8 stages: (1) defining the problem and determine a solution, (2) creating a hierarchical structure, (3) making  pairs comparison matrix, (4) Perform pairs comparisons, (5) calculating the Eigen values and tested for consistency, (6) repeating steps 3,4, and 5 for all levels of hierarchy, (7) calculating the eigen vectors of each matrix comparisons, and (8) checking the consistency of the hierarchy. The input of these applications in the form of the data fields in each district, while the output in the form of the results of the calculation of the percentage of the land. The testing process used black box (functional) testing and white box (conceptual / structural) testing.The type of research used in this study was Research and Development (R & D). Development of geographical information systems productive and nonproductive land in Bali used the web-based Waterfall model with time allocation around six months from September 2012 to January 2013.The result of this research was the Web Based Geographic Information Systems Productive and Non Productive Land in Bali were implemented into Web-based programming language PHP. Based on trial results, it can be seen that these applications were able to perform calculations AHP to determine the percentage for each field. So it can be concluded that the "Web Based Geographic Information Systems and Non Productive Land in Bali' can help people to determine the feasibility of land in an area.